Normative values to assess functional fitness in older adults in a region of Chile - Cossio-Bolaños, Marco; Vidal-Espinoza, Rubén; Castelli Correia de Campos, Luis F.; Sulla-Torres, Jose; Urra-Albornoz, Camilo; Alvear-Vasquez, Fernando; Fuentes-Lopez, Jose; Ramos de Lazari, Marcella Silva; Gomez-Campos, Rossana (Frontiers in Aging, 2025)
IntroductionAging is a global phenomenon that has generated great concerns and challenges in terms of public health and medical care, associated with a lower quality of life. The objective to study was to compare the functional fitness of older adults in a region of Chile with other countries, and to propose normative values according to age range and sex.MethodsA descriptive cross-sectional study was carried out in older adults of the central-south region of Chile. The sample selection was non-probabilistic. A total of 787 older adults (180 males and 607 females) with an age range of 60–85 years were investigated. The sample represents a group of physically active older adults. Weight and height were assessed. Body mass index (BMI) was calculated. The four physical tests evaluated were: 30-s push-up (reps), 30-s standing chair (rep), 8-ft up-and-go (sec), 2-min step test (rep) and 6-min walk (m). Percentiles were calculated for p10, p25, p50, p75 and p90), through the LMS method (L: Lambda; skewness), M: Mu; median and S: Sigma; coefficient of variation).ResultsDiscrepancies in BMI were observed between countries (in males from ∼4.3 to 7.0 kg/m2 and in females from ∼6.7–7.5 kg/m2). In the 30-s push-up test) there were variations from ∼3 to six repetitions in both sexes. In the 8-ft up-and-go test, discrepancies ranged from ∼1.1 to 4.4 s. In the aerobic 2-min step test, discrepancies ranged in both sexes from ∼21 to 41 repetitions. In the 6-min walk test, the variations between studies ranged from ∼150 to 245 m in both sexes. In the 30-s standing chair test, performance in both sexes was relatively homogeneous, varying from ∼1 to 2 repetitions. Percentiles by age range and sex were developed for BMI and the five functional fitness tests.ConclusionThis study demonstrated that there were discrepancies in BMI and functional fitness performance of older adults between countries in various geographic regions of the world. In addition, the proposed percentiles are an important tool to track individual changes and can be used to evaluate and plan intervention programs in older adults in Chile.